Piezoelectric ceramic for piezoelectric ceramic fan and preparation method thereof

By adding rare earth elements into piezoelectric ceramic materials to activate the ferroelectric domain, the problems of low cooling capacity and insufficient temperature stability of piezoelectric ceramic fans are solved, high voltage electrical coefficient and good temperature stability are achieved, and the fatigue resistance and reliability of the device are improved.

CN119591400AActive Publication Date: 2025-03-11XI AN JIAOTONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411033962.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-03-11
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The existing piezoelectric ceramic fans have low cooling capacity and cannot provide high wind pressure compared to traditional fans. At the same time, their performance and reliability may be affected in high temperature environments for a long period of time.

Method used

By adding rare earth elements into piezoelectric ceramic materials, the ferroelectric domains are activated and their piezoelectric activity under external electric field or mechanical stress is improved, thereby improving the piezoelectric coefficient and temperature stability.

Benefits of technology

The high voltage electrical coefficient of piezoelectric ceramics (up to 1700pC/N) and good temperature stability are achieved, and the fatigue resistance is enhanced, ensuring that the device's piezoelectric coefficient only decreases by 10% after 100 million cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591400A_ABST
    Figure CN119591400A_ABST
Patent Text Reader

Abstract

The invention discloses a piezoelectric ceramic for a piezoelectric ceramic fan and a preparation method thereof, the chemical formula of the ceramic material is m% Me2O3-(1-x-y-z) Pb (Mg1 / 3Nb2 / 3) O3-xPb (Zn1 / 2Nb2 / 3) O3-yPbTiO3-zPbZrO3, Me is any one or two of Pr, Ho, Eu, Dy, Nd, Yb, La, Sm, Y, Er and Lu, m% refers to the molar percentage of Me2O3 in (1-x-y-z) Pb (Mg1 / 3Nb2 / 3) O3-xPb (Zn1 / 2Nb2 / 3) O3-yPbTiO3-zPbZrO3, 0.05 < = x < = 0.8, 0.05 < = y < During preparation, step-by-step synthesis and two-step sintering are adopted, the component gradient and proportion can be regulated and controlled, obtained ceramic grains are fine and uniform and high in density, Me2O3 rare earth element is doped into a multiphase piezoelectric ceramic matrix, good temperature stability and high piezoelectric coefficient are obtained within the range of-60 DEG C to 120 DEG C, and d33 is not lower than 1695 pC / N. The piezoelectric ceramic fan has important application in the field of piezoelectric ceramic fans, and is expected to be widely applied in the fields of precise positioning systems, medical imaging equipment, sensors and actuators, energy collection and conversion, consumer electronics, unmanned aerial vehicles and micro aircrafts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of piezoelectric ceramic materials, and in particular relates to a piezoelectric ceramic used for a piezoelectric ceramic fan and a preparation method thereof. Background Art

[0002] A piezoelectric fan is a device that uses the piezoelectric effect to drive the fan blades to rotate. The piezoelectric effect refers to the fact that certain materials generate voltage when subjected to mechanical stress, and vice versa. When voltage is applied to these materials, they change shape or size. In a piezoelectric fan, this physical phenomenon is used to generate mechanical motion to drive the fan to rotate. Piezoelectric fans usually use piezoelectric ceramics as driving elements. When voltage is applied to the piezoelectric ceramic, it will produce a slight change in shape. This deformation is converted into rotation or vibration of the fan blades through a series of mechanical structures, thereby generating airflow. The characteristic of this fan is that there is no traditional motor-driven part, so it can achieve a very small and lightweight design, and low noise during operation, which is very suitable for occasions that require a quiet operating environment. Due to their unique working principle and advantages, piezoelectric ceramic fans are particularly suitable for heat dissipation in portable electronic devices such as smartphones, tablets and other devices. Due to their small size, they can be easily integrated into compact spaces; medical equipment, especially noise-sensitive equipment such as hearing aids and other wearable medical devices; precision instruments, in which temperature control is required but space is very limited, piezoelectric fans can provide effective heat dissipation solutions; consumer electronics, in environments that require silent operation, such as small fans or air purifiers in offices or sleeping areas.

[0003] Although piezoelectric ceramic fans provide a unique and effective cooling method, their cooling capacity may be lower than that of traditional fans, and piezoelectric ceramic fans generally cannot provide greater wind pressure than traditional fans. Therefore, they may not be suitable for applications that require a large amount of air flow. In view of the pain points of this piezoelectric ceramic fan, it is necessary to prepare piezoelectric ceramics with high piezoelectric coefficients to solve this problem. Although piezoelectric ceramics themselves are quite stable and durable, their performance and reliability may be affected in high temperature environments for a long time. Therefore, piezoelectric ceramics with good temperature stability and high piezoelectric coefficients are developed as driving elements to solve the durability and wind pressure of piezoelectric ceramic fans. Summary of the invention

[0004] In view of the defects of low piezoelectric coefficient and insufficient temperature stability of existing piezoelectric materials, the present invention provides a piezoelectric ceramic for a piezoelectric ceramic fan and a preparation method thereof. While maintaining the piezoelectric ceramic material at a relatively high Curie temperature, the ferroelectric domains of the piezoelectric ceramic material are activated to facilitate the movement of the ferroelectric domains. Therefore, they show relatively high piezoelectric activity under the action of an external electric field or mechanical stress. The property of domain rearrangement enables the piezoelectric ceramic to have a relatively high piezoelectric coefficient and good temperature stability.

[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a piezoelectric ceramic for a piezoelectric ceramic fan, the chemical formula of which is m% Me2O3-(1-xyz)Pb(Mg 1 / 3 Nb 2 / 3 )O3-xPb(Zn 1 / 2 Nb 2 / 3 )O3-yPbTiO3-zPbZrO3, wherein Me is any one or two of Pr, Ho, Eu, Dy, Nd, Yb, La, Sm, Y, Er, Lu, and m% refers to the proportion of Me2O3 in m%Me2O3-(1-xyz)Pb(Mg 1 / 3 Nb 2 / 3 )O3-xPb(Zn 1 / 2 Nb 2 / 3 )O3-yPbTiO3-zPbZrO3, 0.05≤x≤0.8, 0.05≤y≤0.8, 0.05≤z≤0.8, 0.01≤m≤5.0 includes four main phase solid solutions, the first phase is Pb(Mg 1 / 3Nb 2 / 3 )O3, the second phase is Pb(Zn 1 / 3 Nb 2 / 3 )O3, the third phase is PbTiO3, and the fourth phase is PbZrO3.

[0006] Furthermore, 0.1≤x≤0.6, 0.1≤y≤0.6, 0.1≤z≤0.6, m=1.5.

[0007] Furthermore, the volume proportions of the first phase, the second phase, the third phase and the fourth phase are 25%, 5%, 30% and 40% respectively.

[0008] The present invention also provides a method for preparing the above material, comprising the following steps:

[0009] Step 1, ball-milling Me2O3 with anhydrous ethanol as a medium until the particle size is nanometer-scale, and drying at 80° C. to obtain nanometer-scale Me2O3 powder;

[0010] Step 2: synthesize Pb(Mg 1 / 3 Nb2 / 3 )O3 Pb(Zn 1 / 3 Nb 2 / 3 )O3, PbTiO3, PbZrO3;

[0011] Step 3, according to m%Me2O3-(1-xyz)Pb(Mg 1 / 3 Nb 2 / 3 )O3-xPb(Zn 1 / 3 Nb 2 / 3 )O3-yPbTiO3-zPbZrO3 stoichiometric ratio, Me2O3 powder, Pb(Mg 1 / 3 Nb 2 / 3 )O3、Pb(Zn 1 / 3 Nb 2 / 3 )O3, PbTiO3, and PbZrO3 are mixed, ball-milled to nanometer particle size using anhydrous ethanol as a medium, and then heated in a furnace after drying, and pre-calcined at 750-1050°C for 2-6 hours;

[0012] Step 4, granulating the powder obtained after pre-calcining in step 3 with a polyvinyl alcohol aqueous solution with a weight concentration of 5%, and pressing it into discs, and heating the formed discs with a furnace, keeping them at 600° C.-650° C. for 2 hours to remove the polyvinyl alcohol;

[0013] Step 5, heating the wafer after removing polyvinyl alcohol in step 4 to 1000-1350° C., immediately cooling it to 800-1100° C., and keeping it warm for 2-3 hours; obtaining the above.

[0014] Furthermore, in step 3, pre-calcination is performed at 1020-1050° C. for 2-3 hours.

[0015] Furthermore, in step 5, the wafer after removing PVA in step 4 is first heated to 1200-1300° C. without heat preservation, and then cooled to 1080-1100° C. and kept warm for 3 hours.

[0016] Furthermore, the Me2O3 powder is nano-scale Me2O3 powder that has been wet ball-milled and dried.

[0017] Furthermore, Pb(Mg 1 / 3 Nb 2 / 3 )O3 has an average particle size of 100nm, Pb(Zn 1 / 3 Nb 2 / 3 )O3 has an average particle size of 200nm, PbTiO3 has an average particle size of 100nm, and PbZrO3 has an average particle size of 300nm.

[0018] Furthermore, in step 3 and step 4, the heating rate is 3°C / min, and in step 5, the cooling rate is 10°C / min.

[0019] Furthermore, the obtained 33 Not less than 1695pC / N.

[0020] Compared with the prior art, the present invention has at least the following beneficial effects:

[0021] The present invention aims at the lower piezoelectric coefficient of piezoelectric ceramics for piezoelectric ceramic fans, and obtains a high and stable piezoelectric coefficient by adding an appropriate amount of rare earth element Me into the multiphase piezoelectric ceramic matrix. The main principle is to use rare earth elements to activate ferroelectric domains, improve the activity of ferroelectric domains, and make it relatively easy for the domains to rearrange under an external electric field, which means that they can achieve efficient polarization under a lower electric field and improve the piezoelectric coefficient of the material. The piezoelectric coefficient of the piezoelectric ceramic of the present invention can be as high as 1700pC / N. At the same time, the piezoelectric coefficient of the ceramic material shows good stability in the range of -60 to 120°C, and after the introduction of rare earth elements to activate the ferroelectric domains, the fatigue resistance of the ceramic is greatly enhanced, and the piezoelectric coefficient of the device only decreases by 10% after 100 million cycles. These characteristics indicate that the piezoelectric ceramics of the present invention are expected to be used in the field of piezoelectric ceramic fans; the present invention adopts step-by-step synthesis and two-step sintering, and the composition gradient and proportion can be adjusted. The obtained ceramic grains are small and uniform, with high density, which can meet the needs of different applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the X-ray diffraction pattern of the ceramic material prepared in Example 1.

[0023] Figure 2 This is a scanning electron microscope image of the ceramic material prepared in Example 1.

[0024] Figure 3 This is a graph showing how the dielectric constant and dielectric loss of the ceramic material prepared in Example 1 vary with temperature.

[0025] Figure 4 This is the hysteresis loop of the ceramic material prepared in Example 1. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0027] Example 1

[0028] Step 1. Mill La2O3 with a purity of 99.99% using anhydrous ethanol as a medium for 12 hours and dry at 150°C to obtain Me2O3 powder;

[0029] Step 2. Take 122.46g of 99.99% pure Pb3O4, 7.53g of 99.99% pure MgCO3, and 47.48g of 99.99% pure Nb2O5 and put them into a ball mill, and mix them for 12 hours according to the volume ratio of the raw material mixture, agate balls, and anhydrous ethanol of 1:2:4, and then bake them in an oven at 80°C for 10 hours. After drying, the raw material mixture is pressed into a round green embryo with a diameter of 60mm at 0.1MPa by a tablet press. The round green embryo after pressing is placed in a muffle furnace and kept at 800°C for 3 hours, and then crushed to obtain Pb (Mg) with a pure perovskite structure. 1 / 3 Nb 2 / 3 )O3.

[0030] 118.13g of 99.99% pure Pb3O4, 7.01g of 99.99% pure ZnO, and 45.8g of 99.99% pure Nb2O5 were put into a ball mill, and the raw material mixture, agate balls, and anhydrous ethanol were mixed by ball milling for 12 hours according to a volume ratio of 1:2:4, and then dried in an oven at 80°C for 10 hours. After drying, the raw material mixture was pressed into a round green embryo with a diameter of 60mm at 0.1MPa by a tablet press. The round green embryo after tableting was placed in a muffle furnace and kept at 850°C for 5 hours, and then crushed to obtain Pb (Zn) with an average particle size of about 200nm. 1 / 3 Nb 2 / 3 )O3 powder.

[0031] 130.2g of 99.99% pure Pb3O4 and 22.75g of 99.99% pure TiO2 were put into a ball mill, and the raw material mixture was mixed with agate balls and anhydrous ethanol in a volume ratio of 1:2:4 for 12 hours, and then dried in an oven at 80°C for 10 hours. After drying, the raw material mixture was pressed into a round green embryo with a diameter of 60mm at 0.1MPa by a tablet press, and the round green embryo after pressing was placed in a muffle furnace at 850°C for 5 hours, and crushed to obtain PbTiO3 with an average particle size of about 100nm.

[0032] 115.88g of 99.99% pure Pb3O4 and 31.24g of 99.99% pure ZrO2 were put into a ball mill, and the raw material mixture was mixed with agate balls and anhydrous ethanol in a volume ratio of 1:2:4 for 12 hours, and then dried in an oven at 80°C for 10 hours. After drying, the raw material mixture was pressed into a round green embryo with a diameter of 60mm at 0.1MPa by a tablet press, and the round green embryo after pressing was placed in a muffle furnace at 850°C for 5 hours, and crushed to obtain PbZrO3 with an average particle size of about 300nm.

[0033] Step 3. According to 1.5at.%La2O3-0.25Pb(Mg 1 / 3 Nb2 / 3 )O3-0.05Pb(Zn 1 / 3 Nb 2 / 3 )The stoichiometric ratio of PbO3-0.3PbTiO3-0.4PbZrO3 was determined. The raw materials were weighed separately and put into a ball mill. The raw material mixture, agate balls and anhydrous ethanol were mixed by ball milling at a volume ratio of 1:2:4 for 12 hours. After ball milling, the mixture was dried in an oven at 80°C and then pre-calcined in a muffle furnace at 1050°C for 2 hours.

[0034] Step 4. Add 2 mL of a 5% by weight polyvinyl alcohol aqueous solution as a binder to the powder obtained after pre-calcination in step 3 to make granules, mix them thoroughly in a mortar and pass them through a 200-mesh sieve; press the granulated powder into a disc with a thickness of 1.2 mm and a diameter of 12.00 mm at 200 MPa, and keep the formed disc at 600°C for 2 hours to remove the polyvinyl alcohol.

[0035] Step 5. The wafer after removing the polyvinyl alcohol in step 4 was heated to 1280°C, without heat preservation, and then rapidly cooled to 1100°C, and kept at this temperature for 2 hours at a cooling rate of 10°C / min to obtain a ceramic material 1.5at.%La2O3-0.25Pb(Mg 1 / 3Nb 2 / 3 )O3-0.05Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.3PbTiO3-0.4PbZrO3.

[0036] The phase structure of the ceramic material prepared in this example was measured by X-ray diffractometer. Figure 1 As shown in Figure 2, XRD data show that the material is a pure perovskite phase with no impurity generated. Figure 2 The scanning electron microscope image shows that the prepared ceramic is very dense and has uniform grain size. The ceramic material is further processed into a thin sheet with smooth surfaces and a thickness of about 1.0 mm. Electrodes are plated on both sides, and the dielectric temperature spectrum and hysteresis loop of the ceramic material are measured. Figure 3 and 4 As shown. Figure 3 It can be seen that the piezoelectric coefficient of the ceramic material shows good stability in the range of -60 to 120°C. Figure 4 It can be seen that the ceramic material has no internal bias electric field. 33 After the test, the tester gets d 33 It is 1700pC / N.

[0037] Example 2

[0038] In step 3 of this embodiment, 5.91 g of Yb2O3 with a purity of 99.99% was used to replace the La2O3 in Example 1, and the mixture was prepared according to the conditions of 1.5 at.% Yb2O3-0.1Pb(Mg1 / 3 Nb 2 / 3 )O3-0.8Pb(Zn 1 / 3 Nb 2 / 3 The raw materials were weighed and put into a ball mill according to the volume ratio of the raw material mixture, agate balls and anhydrous ethanol of 1:2:4 for 10 hours, and then dried in an oven at 80°C, and then pre-calcined in a muffle furnace at 750°C for 6 hours.

[0039] Step 4. Add 2 mL of a 5% by weight aqueous solution of polyvinyl alcohol to the powder obtained after pre-calcination in step 3 as a binder for granulation, mix thoroughly in a mortar and pass through a 200-mesh sieve; press the granulated powder into a disc with a thickness of 1.2 mm and a diameter of 12.00 mm at 200 MPa, and keep the formed disc at 650°C for 2 hours to remove the polyvinyl alcohol.

[0040] Step 5. The wafer after removing the polyvinyl alcohol in step 4 was heated to 1000°C without heat preservation, and then rapidly cooled to 800°C and kept at this temperature for 2 hours to obtain a ceramic material 1.5at.% Yb2O3-0.1Pb(Mg 1 / 3 Nb 2 / 3 )O3-0.8Pb(Zn 1 / 3 Nb 2 / 3 )O3 -0.05PbTiO3-0.05PbZrO3, quasi-static d 33 After the test, the tester gets d 33 It is 1705pC / N.

[0041] Example 3

[0042] In step 3 of this embodiment, 5.05 g of Nd2O3 with a purity of 99.99% was used to replace the La2O3 in embodiment 1, and the mixture was prepared according to the conditions of 1.5 at.% Nd2O3-0.1Pb(Mg 1 / 3 Nb 2 / 3 )O3-0.05Pb(Zn 1 / 3 Nb 2 / 3 )O3 -0.8PbTiO3-0.05PbZrO3 stoichiometric ratio, weigh the raw materials separately and put them into a ball mill, mix them for 10 hours with the raw material mixture, agate balls and anhydrous ethanol in a volume ratio of 1:2:4, dry them in an oven at 80°C after ball milling, and then pre-calculate them in a muffle furnace at 900°C for 4 hours.

[0043] Step 4. Add 2 mL of a 5% by weight aqueous solution of polyvinyl alcohol to the powder obtained after pre-calcination in step 3 as a binder for granulation, mix thoroughly in a mortar and pass through a 200-mesh sieve; press the granulated powder into a disc with a thickness of 1.2 mm and a diameter of 12.00 mm at 200 MPa, and keep the formed disc at 650°C for 2 hours to remove the polyvinyl alcohol.

[0044] Step 5. The wafer after removing the polyvinyl alcohol in step 4 was heated to 1000°C without heat preservation, and then rapidly cooled to 800°C and kept at this temperature for 2.5 hours to obtain a ceramic material 1.5at.% Nd2O3-0.1Pb(Mg 1 / 3 Nb 2 / 3 )O3-0.05Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.8PbTiO3-0.05PbZrO3, quasi-static d 33 After the test, the tester gets d 33 It is 1695pC / N.

[0045] Example 4

[0046] In this embodiment, 5.28 g of Eu2O3 with a purity of 99.99% was used to replace the La2O3 in Example 1. The other steps were the same as in Example 1 to obtain a ceramic material 1.5 at.% Eu2O3-0.05Pb(Mg 1 / 3 Nb 2 / 3 )O3-0.1Pb(Zn 1 / 3 Nb 2 / 3 )O3 -0.05PbTiO3-0.8PbZrO3, quasi-static d 33 After the test, the tester gets d 33 It is 1996pC / N.

[0047] Example 5

[0048] In step 3 of this embodiment, according to 1.5at.% La2O3-0.26Pb(Mg 1 / 3 Nb 2 / 3 )O3-0.04Pb(Zn 1 / 3Nb 2 / 3 )O3-0.29PbTiO3-0.41PbZrO3 stoichiometric ratio, weigh the raw materials separately and put them into a ball mill, mix them for 12 hours according to the volume ratio of raw material mixture, agate ball and anhydrous ethanol of 1:2:4, dry them in an oven at 80℃ after ball milling, and then pre-sinter them in a muffle furnace at 1000℃ for 2 hours. Heat the disc after removing polyvinyl alcohol to 1250℃ without heat preservation, and then quickly cool it to 1000℃ and keep it for 2.5 hours to obtain the ceramic material 1.5at.%La2O3-0.26Pb(Mg1 / 3 Nb 2 / 3 )O3-0.04Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.29PbTiO3-0.41PbZrO3, quasi-static d 33 After the test, the tester gets d 33 It is 1729pC / N.

[0049] Example 6

[0050] In step 3 of this embodiment, according to 1.5at.%Eu2O3-0.4Pb(Mg 1 / 3 Nb 2 / 3 )O3-0.2Pb(Zn 1 / 3 Nb 2 / 3 )O3-0.2PbTiO3-0.2PbZrO3 stoichiometric ratio, weigh the raw materials respectively and put them into the ball mill, mix them by ball milling for 12 hours according to the volume ratio of raw material mixture, agate ball and anhydrous ethanol of 1:2:4, dry them in an oven at 80℃ after ball milling, and then pre-sinter them in a muffle furnace at 950℃ for 2 hours. Heat the disc after removing polyvinyl alcohol to 1200℃ without heat preservation, and then quickly cool it to 950℃ and keep it for 2.5 hours to obtain the ceramic material 1.5at.%Eu2O3-0.4Pb(Mg 1 / 3 Nb 2 / 3 )O3-0.2Pb(Zn 1 / 3 Nb 2 / 3 )O3 -0.2PbTiO3-0.2PbZrO3, quasi-static d 33 After the test, the tester gets d 33 It is 1906pC / N.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A piezoelectric ceramic for a piezoelectric ceramic fan, characterized in that: The chemical formula is m%Me2O3-(1-xyz)Pb(Mg 1 / 3 Nb 2 / 3 )O3-xPb(Zn 1 / 2 Nb 2 / 3 )O3-yPbTiO3-zPbZrO3, wherein Me is any one or two of Pr, Ho, Eu, Dy, Nd, Yb, La, Sm, Y, Er, Lu, and m% refers to the proportion of Me2O3 in m%Me2O3-(1-xyz)Pb(Mg 1 / 3 Nb 2 / 3 )O3-xPb(Zn 1 / 2Nb 2 / 3 )O3-yPbTiO3-zPbZrO3, 0.05≤x≤0.8, 0.05≤y≤0.8, 0.05≤z≤0.8, 0.01≤m≤5.0 includes four main phase solid solutions, the first phase is Pb(Mg 1 / 3 Nb 2 / 3 )O3, the second phase is Pb(Zn 1 / 3 Nb 2 / 3 )O3, the third phase is PbTiO3, and the fourth phase is PbZrO3.

2. The piezoelectric ceramic for a piezoelectric ceramic fan according to claim 1, characterized in that: 0.1≤x≤0.6, 0.1≤y≤0.6, 0.1≤z≤0.6, m=1.

5.

3. The piezoelectric ceramic for a piezoelectric ceramic fan according to claim 1, characterized in that: The volume proportions of the first phase, the second phase, the third phase and the fourth phase are 25%, 5%, 30% and 40% respectively.

4. A method for preparing a piezoelectric ceramic for a piezoelectric ceramic fan according to any one of claims 1 to 3, characterized in that: The steps include: Step 1, ball-milling Me2O3 with anhydrous ethanol as a medium until the particle size is nanometer-scale, and drying at 80° C. to obtain nanometer-scale Me2O3 powder; Step 2: synthesize Pb(Mg 1 / 3 Nb 2 / 3 )O3 Pb(Zn 1 / 3 Nb 2 / 3 )O3, PbTiO3, PbZrO3; Step 3, according to m%Me2O3-(1-xyz)Pb(Mg 1 / 3 Nb 2 / 3 )O3-xPb(Zn 1 / 3 Nb 2 / 3 )O3-yPbTiO3-zPbZrO3 stoichiometric ratio, Me2O3 powder, Pb(Mg 1 / 3 Nb 2 / 3 )O3、Pb(Zn 1 / 3 Nb 2 / 3 )O3, PbTiO3, and PbZrO3 are mixed, ball-milled to nanometer particle size using anhydrous ethanol as a medium, and then heated in a furnace after drying, and pre-calcined at 750-1050°C for 2-6 hours; Step 4, granulating the powder obtained after pre-calcining in step 3 with a polyvinyl alcohol aqueous solution with a weight concentration of 5%, and pressing it into discs, and heating the formed discs with a furnace, keeping them at 600° C.-650° C. for 2 hours to remove the polyvinyl alcohol; Step 5, heating the wafer after removing polyvinyl alcohol in step 4 to 1000-1350° C., immediately cooling it to 800-1100° C., and keeping it warm for 2-3 hours; obtaining the above.

5. The method for preparing piezoelectric ceramics for a piezoelectric ceramic fan according to claim 4, characterized in that: In step 3, pre-sintering is performed at 1020-1050° C. for 2-3 hours.

6. The method for preparing piezoelectric ceramics for a piezoelectric ceramic fan according to claim 4, characterized in that: In step 5, the wafer after PVA is removed in step 4 is first heated to 1200-1300° C. without heat preservation, and then cooled to 1080-1100° C. and kept warm for 3 hours.

7. The method for preparing piezoelectric ceramics for a piezoelectric ceramic fan according to claim 4, characterized in that: The Me2O3 powder is nano-sized Me2O3 powder that has been wet ball-milled and dried.

8. The method for preparing piezoelectric ceramics for a piezoelectric ceramic fan according to claim 4, characterized in that: Pb(Mg 1 / 3 Nb 2 / 3 )O3 has an average particle size of 100nm, Pb(Zn 1 / 3 Nb 2 / 3 )O3 has an average particle size of 200nm, PbTiO3 has an average particle size of 100nm, and PbZrO3 has an average particle size of 300nm.

9. The method for preparing piezoelectric ceramics for a piezoelectric ceramic fan according to claim 4, characterized in that: In step 3 and step 4, the heating rate is 3°C / min, and in step 5, the cooling rate is 10°C / min.

10. The method for preparing piezoelectric ceramics for a piezoelectric ceramic fan according to claim 4, characterized in that: Income 33 Not less than 1695pC / N.

Citation Information

Patent Citations

  • Submicron-crystal-scale piezoelectric energy collecting material and preparation method thereof

    CN107056291A

  • Lead zirconate titanate-manganese bismuth based perovskite-lead based composite perovskite multi-component low-temperature sintered large-power piezoelectric ceramic, and preparation method thereof

    CN109956748A

  • PMNZT-based piezoelectric ceramic with high piezoelectric coefficient as well as preparation method and application of PMNZT-based piezoelectric ceramic

    CN115894020A

  • Hard piezoelectric ceramic material with high mechanical quality factor and preparation method thereof

    CN115894021A

  • Artificial synaptic memristive device sensitive to environmental factors and preparation method of artificial synaptic memristive device

    CN118401091A